Upaya Peningkatan Kualitas Politisi Muda Melalui Pelatihan dan Pendidikan Politik Yayasan SATUNAMA Yogyakarta - Firdha Eka Susanti Dianingsih (Edumedia Solution, 2022)
Political education is a form of sign that we are helping to build a better state politics. Political education in politicians is a distribution to prospective leaders who will represent the community. With an unhealthy political image in Indonesia, it starts with the number of corruption figures revealed by government officials. Ignorance and generally a